Study of the relationship between the severity of downy mildew infection in cucumber and its content of phenols and alkaloids under protected cultivation conditions - Khudhair, A A; Aljarah, N S (Plant Science Today, 2025)
The study was carried out to investigate the distribution pattern and intensity of downy mildew disease in three different parts of cucumber plants (upper, middle and lower). Additionally, the study aimed to examine the correlation between the disease severity and the concentration of phenolic and alkaloid compounds in the plants. Under controlled greenhouse conditions, the results demonstrated that the cucumber plants had the most significant disease severity at the middle level, followed by the lower level near the ground. Conversely, no signs of infection were detected at the higher level of the plant. Furthermore, the most severe downy mildew symptoms were noticed in the greenhouses central region, compared to the areas near the front and back entrances. These differences were shown to be statistically significant. Before the onset of downy mildew infection, cucumber plants indicated minimal phenols and alkaloids. From the first day of infection, the concentration of phenols increased and peaked on the twelfth day following infection. Subsequently, it declined on the 15th day. The level of alkaloids peaked on the sixth day of disease infection and then gradually decreased. The cucumber plants exhibited the highest concentrations of phenols and alkaloids around the ground level, followed by the middle and upper levels These variations were statistically significant. The highest correlation coefficient was reported between the disease severity and the cucumbers content of alkaloids and phenols at the middle and the lower level of the two hybrids: Jamila and Mustaqbal. In the Fares hybrid, the highest correlation coefficient between the percentage of disease severity and phenols was 0.905 at the middle level, but it was 0.434 with the alkaloid contents. At the lower level of the plants, the correlation coefficient between disease severity with the alkaloids and phenols was 0.724 and 0.725, respectively.